Studies on combining ability and heterosis for seed yield and its attributing traits in sunflower: Studies on combining ability and heterosis for seed yield and its attributing traits in sunflower - S D NEHRU,; B NIHARIKA,; M S UMA,; K M SRINIVAS REDDY, (Journal of Oilseeds Research, 2020)
Field experiment was conducted to estimate the combining ability and heterotic effects of sunflower hybrids. Twelve lines and six testers were crossed in Line×Tester mating design to generate 72 hybrids, which were further evaluated in kharif summer 2018 along with checks KBSH-41, KBSH-42, KBSH-44 and KBSH-53 at UAS, GKVK, Bengaluru. The seed parent, CMS 17B was a better general combiner for stem diameter, head diameter, seed yield/plant, hundred seed weight and oil content followed by CMS103B (B). The tester, RHA 95 C-10 was identified as desirable general combiner for stem diameter, head diameter, seed yield/plant, volume weight, hundred seed weight, oil content and oil yield. The cross combination CMS 335 A × RHA 95 C10 exhibited better per se performance and standard heterosis for seed yield/plant and oil content followed by CMS 56 A × RHA GMU 762 and CMS 911 A × RHA GMU 755. Further the lines (CMS 17, CMS 335, CMS 597) and the testers (RHA 95C-10, RHA 278) should be preferentially used in hybrid development and testing for commercial exploitation. The cross combinations like CMS 335A × RHA 95C-10 and CMS 911A × RHA GMU 755 with high SCA need to be confirmed for their superiority by large scale testing as multi locational trials.